2018
DOI: 10.1159/000491891
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Bushen Formula Combined with Enticavir on Chronic Hepatitis B Patients with Suboptimal Response to Enticavir by Regulating B-Cell Differentiation

Abstract: Background/Aims: To investigate the clinical effects of the combination therapy with Bushen Formula (BSF) plus enticavir (ETV) on chronic hepatitis B (CHB) patients with suboptimal response to ETV and explore the regulatory mechanisms of BSF on B cells-mediated humoral immunity. Methods: Sixty-four HBeAg-positive CHB patients with suboptimal response to ETV were enrolled, and were randomly assigned into control group (C-Group, placebo combined with ETV for 12 months) or treatment group (T-Group, BSF combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Especially with long-term clinical application, TCM has been widely accepted as a safe and effective treatment for CHB and CG in China (Li et al, 2020;Li, Li, & Tan, 2021;Wu et al, 2020). Recent studies have shown that TCM can enhance the body's immunity to combat pathogenic microorganisms and favor the alleviation of clinical symptoms, as well as improve patients' quality of life (Li et al, 2018;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Especially with long-term clinical application, TCM has been widely accepted as a safe and effective treatment for CHB and CG in China (Li et al, 2020;Li, Li, & Tan, 2021;Wu et al, 2020). Recent studies have shown that TCM can enhance the body's immunity to combat pathogenic microorganisms and favor the alleviation of clinical symptoms, as well as improve patients' quality of life (Li et al, 2018;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…another clinical research shows that combination therapy of traditional chinese medicine plus ETV for 48 weeks resulted in a higher rate of necro in ammatory improvement and brosis regression than ETV alone in CHB patients with serious liver brosis/cirrhosis. [14][15] The above researches have proven that TCM plays an important role in the prevention and treatment of liver brosis, however, there is still lacking of large-sample, multi-center randomized controlled studies to provide reliable and high-level evidencebased medical evidence for the prevention and treatment of liver brosis by TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Alisma Shugan Decoction (ASD), a kind of traditional Chinese medicine compound, ameliorates hepatotoxicity and associated liver dysfunction by inhibiting oxidative stress and p65/Nrf2/JunD signaling dysregulation in vivo [ 13 ]. Clinical study has reported that the integrative medicine therapy (ETV plus TCM) can promote the reduction of HBsAg level and the clearance of HBeAg in CHB patients with partial response to ETV through regulating the differentiation of B-cell subsets; another clinical research shows that combination therapy of traditional Chinese medicine plus ETV for 48 weeks resulted in a higher rate of necroinflammatory improvement and fibrosis regression than ETV alone in CHB patients with serious liver fibrosis/cirrhosis [ 14 , 15 ]. The above researches have proven that TCM plays an important role in the prevention and treatment of liver fibrosis; however, there is still lacking of large-sample, multi-center randomized controlled studies to provide reliable and high-level evidence-based medical evidence for the prevention and treatment of liver fibrosis by TCM.…”
Section: Introductionmentioning
confidence: 99%